Dinamika Psikologis Dark Jokes: Antara Mekanisme Coping Adaptif dan Respon Maladaptif terhadap Pengalaman Duka - Ananda Dwi Pratiwi; Muhammad Basir; Muhammad Fadland (Sultan Idris Journal of Psychology and Education, 2026)
Abstract Dark jokes or dark humor is a form of humor that raises sensitive themes such as death, trauma, and loss. From a psychological perspective, dark humor is not only understood as a joke, but also as an individual's way of dealing with emotional distress and grief experiences. This study aims to examine the use of dark jokes from a psychological perspective, especially related to coping mechanisms, emotion regulation, and defense mechanisms. The research uses the Systematic Literature Review method with a qualitative descriptive approach through the search of various scientific articles and relevant academic sources. The results of the study show that dark humor has an ambiguous psychological function. On the one hand, dark humor can help individuals reduce emotional distress, create emotional distance, and maintain psychological stability when dealing with loss. However, on the other hand, dark humor can also be maladaptive when used in the form of verbal aggressiveness or excessive emotional avoidance. Therefore, the use of dark jokes is influenced by the individual's psychological state, social context, and the purpose of using humor itself.